The Truffles in Mamlukian Inscription from Jordanian Badia which Dated on 767 H. - Al-Jbour, Khaled (Dirasat: Human and Social Sciences, 2022)
This study is concerned with an inscription from Mamlukian period discovered by the researcher in eastern Badia of Jordan in site called Ghadeer al-Dahab southeast of the town Al-Safaweabout 50 km. The inscription provides us information about the pastured and gathered the truffles which is reflection to the economic situation for the Bedouins tribes. The inscriber mentioned a name of one of the pilgrims and a supplication of forgiveness for him and a verse of poetry about asceticism in life mentioning the pilgrim is very important and give an indication that the location of the inscription was a caravan’s route because there is a trace of track of travelers in that region and in the end of the text.The inscriber dated his inscription at the year 767H/ 1366 Ad.